PROJECT MANAGEMENT OF THE TRANSFORMATION SYSTEM MODEL OF THE CONSTRUCTION BUSINESS - A. Gukasova; I. Brikoshina (Вестник университета, 2017)
In the article have been analyzed the construction industry in Russia and its regions, also considered the current situation in this segment of the economy, the absorption of large companies. Proposed solutions to optimize the construction business.